Altering Compositional Properties of Viral Genomes to Design Live-Attenuated Vaccines - Pereira-Gómez, Marianoel; Carrau, Lucía; Fajardo, Álvaro; Moreno, Pilar; Moratorio, Gonzalo (Frontiers in Microbiology, 2021)
Live-attenuated vaccines have been historically used to successfully prevent numerous diseases caused by a broad variety of RNA viruses due to their ability to elicit strong and perdurable immune-protective responses. In recent years, various strategies have been explored to achieve viral attenuation by rational genetic design rather than using classic and empirical approaches, based on successive passages in cell culture. A deeper understanding of evolutionary implications of distinct viral genomic compositional aspects, as well as substantial advances in synthetic biology technologies, have provided a framework to achieve new viral attenuation strategies. Herein, we will discuss different approaches that are currently applied to modify compositional features of viruses in order to develop novel live-attenuated vaccines.